Thermoelectric convection in a planar capacitor: theoretical studies and experiments in parabolic flights - Barry, Elhadj B.; Yoshikawa, Harunori N.; Kang, Changwoo; Meyer, Antoine; Meier, Martin; Crumeyrolle, Olivier; Egbers, Christoph; Mutabazi, Innocent (Comptes Rendus. Mécanique, 2023)
Thermoelectric convection in a plane capacitor is investigated in a microgravity environment and in the case of the thermal stable and unstable stratification in terrestrial conditions. Energetic analysis shows that in the thermal stable stratification, the thermoelectric convection is delayed while in the thermal unstable stratification, it is enhanced by the Archimedean buoyancy before the latter takes over the dielectrophoretic buoyancy and drives natural thermal convection. An experiment in parabolic flights shows the formation of thermoelectric convection at the end of the microgravity phase.